Wheat Genotype-Specific Recruitment of Rhizosphere Bacterial Microbiota Under Controlled Environments - Dilla-Ermita, Christine Jade; Lewis, Ricky W.; Sullivan, Tarah S.; Hulbert, Scot H. (Frontiers in Plant Science, 2021)
Plants recruit beneficial microbial communities in the rhizosphere that are involved in a myriad of ecological services such as improved soil quality, nutrient uptake, abiotic stress tolerance, and soil-borne disease suppression. Disease suppression caused by rhizosphere microbiomes has been important in managing soil-borne diseases in wheat. The low heritability of resistance in wheat to soil-borne diseases like Rhizoctonia root-rot have made management of these diseases challenging, particularly in direct-seeded systems. Identification of wheat genotypes that recruit rhizosphere microbiomes that promote improved plant fitness and suppression of the pathogen could be an alternative approach to disease management. Several growth-chamber cycling experiments were conducted using six winter wheat genotypes (PI561725, PI561727, Eltan, Lewjain, Hill81, Madsen) to determine wheat genotypes that recruit suppressive microbiomes. At the end of the third cycle, suppression assays were done by inoculating R. solani into soils previously cultivated with specific wheat genotypes to test suppression of the pathogen by the microbiome. Microbiome composition was characterized by sequencing of 16S rDNA (V1-V3 region). Among the growth cycling lengths, 160-day growth cycles exhibited the most distinct rhizosphere microbiomes among the wheat genotypes. Suppression assays showed that rhizosphere microbiomes of different wheat genotypes resulted in significant differences in shoot length (p-value = 0.018) and had an impact on the pathogenicity of R. solani, as observed in the reduced root disease scores. Furthermore, soils previously cultivated with the ALMT1 isogenic lines PI561725 and PI561727, exhibited better seedling vigor and reduced root disease. Microbiome analysis showed that Burkholderiales taxa, specifically Janthinobacterium, are differentially abundant in PI561727 and PI561725 cultivated soils, and are associated with reduced root disease and better growth. This study demonstrates that specific wheat genotypes to recruit different microbiomes in growth chamber conditions but the microbial community alterations were quite different from those previously observed in field plots, even though the same soils were used. Genotype selection or development appears to be a viable approach to controlling soilborne diseases in a sustainable manner and controlled environment assays can be used to see genetic differences but further work is needed to explain differences seen between growth chamber and field conditions.